Pengaruh Employee Engagement, Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai (Studi Pada Pegawai Badan Pendapatan Pengelolaan Keuangan Dan Asset Daerah Kabupaten Bima) - Sri Wasillah; Pardiman Pardiman; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of employee engagement, organizational culture and organizational commitment on employee performance at the regional financial and asset management revenue agency in Bima Regency. The sample in this study amounted to 81 people who are employees of the regional financial and asset management revenue agency, Bima Regency. The sampling technique used is purposive sampling. The data used in the study used primary and secondary data. The method used is descriptive data analysis by using validity, reliability, normality, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, f test, t test and coefficient of determination with the SPSS statistical program IBM Version 22. shows that simultaneously each variable employee engagement, organizational culture and organizational commitment equally affect employee performance, while partially employee engagement variables, organizational culture and organizational commitment have no significant effect on the performance of employees of the district financial and asset management revenue agency. bimaKeywords: Employee Engagement, Organizational Culture, Organizational Commitment, Employee Performance